2018
DOI: 10.3892/ijmm.2018.3937
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant effects of MOK, a polyherbal extract, on lipopolysaccharide‑stimulated RAW 264.7 macrophages

Abstract: MOK, a pharmacopuncture medicine consisting of 10 herbs, has a long history as treatment for various inflammatory conditions. To investigate the mechanisms of action of MOK, its anti-inflammatory and antioxidative effects were assessed in RAW 264.7 macrophages stimulated by lipopoly-saccharide (LPS). RAW 264.7 cells were treated with different concentrations of MOK extract for 30 min prior to stimulation with or without LPS for the indicated times. Nitric oxide (NO) production was measured using Griess reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 40 publications
6
43
0
Order By: Relevance
“…While this implies that the microenvironment may change, which would support tumor growth due to prostaglandin production by COX-2 enzymatic activity, other mechanisms are possible. Decreased levels of COX-2 are relative to the abnormal immune function of macrophages (17,18). In the present study, it was revealed that KLF9, a direct target of GCs, could reduce LPS-induced COX-2 levels, indicating that KLF9 is a potent inhibitor of immune function in macrophages.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…While this implies that the microenvironment may change, which would support tumor growth due to prostaglandin production by COX-2 enzymatic activity, other mechanisms are possible. Decreased levels of COX-2 are relative to the abnormal immune function of macrophages (17,18). In the present study, it was revealed that KLF9, a direct target of GCs, could reduce LPS-induced COX-2 levels, indicating that KLF9 is a potent inhibitor of immune function in macrophages.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, COX-2 has been revealed to modulate the fate of colon cancer cell lines by generating prostanoids (15)(16)(17). These observations indicate that COX-2 expression and prostanoid generation may play a fundamental role in the initiation and promotion of cancers arising from inflamed tissues, such as cholangiocarcinoma (18). However, it is unknown whether COX-2 can modulate apoptosis of immune cells, such as macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of NO were measured using Griess reagent. 23,24 After cell treatment, 100 µL of the supernatant from the cell culture was mixed with 100 µL of Griess reagent and incubated in the dark for 10 minutes at room temperature. The absorbance of the mixture was measured at 550 nm using a microplate reader.…”
Section: Determination Of Nitrite Levelsmentioning
confidence: 99%
“…The LPS is recognized as a pathogen-associated molecular pattern by specific receptors expressed on immune cells, i.e., Toll-like receptors (TLRs), which are then activated. In particular, the LPS interacts with monocytes and macrophages through TLR4 and plays a crucial role in the inflammation process by inducing the production of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin (IL)-6, and the expression of the enzyme cyclooxygenase-2 (COX-2) which controls the formation of several inflammatory mediators catalyzing conversion of arachidonic acid to different prostaglandins including prostaglandin E2 [ 4 , 5 , 6 , 7 , 8 ]. Notably, inflammation is the primary physiological response of the immune system to external and internal stimuli (e.g., infections or tissue injuries), a response that restores the integrity of damaged tissues; the regulation of inflammation is essential for the tissue homeostasis in damaged biological compartments [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%